Societal perception on environmental and socio-economic implications of Tithonia diversifolia (Hemsl.) A. Gray invasion in an Indo-Burma biodiversity hotspot - Rai Prabhat Kumar; Vanlalruati (Environmental & Socio-economic Studies, 2022)
Tithonia diversifolia (Hemsl.) A. Gray is an emerging and little studied plant invader in North East India, an Indo-Burma biodiversity hotspot. Identifying the impacts of its invasiveness in terms of both harmful and economically beneficial facets is required for the formulation and implementation of sustainable management options. An environmental and socio-economic implication survey through the pragmatic questionnaire method is a useful approach to explicitly elucidate the holistic influence of T. diversifolia on ecosystem resilience. The interaction of T. diversifolia with the local people of Mizoram was assessed in this study in terms of its effects on their livelihoods, socio-economic, and ecological factors. Results of the survey in relation to agricultural implications revealed that 42.68% of the respondents opined that the dried litter of T. diversifolia can improve soil fertility. Also, 63.41% people during their interview perceived T. diversifolia as an effective tool to prevent. However, 70.73% of rural people did not consider T. diversifolia to be a good source of livelihood for income generation or socio-economic status. Since, the respondents were not aware of chemical and biological control measures to regulate the spread of invasive alien plant species, physical methods such as slashing (46.34%), burning (13.41%), chopping and burning (29.27%) were widely applied for the control and management of invaded areas of T. diversifolia at selected study sites. Thus, the survey gave a brief idea to the other local people, farmers, and agriculturists of Mizoram to control the invasive spread of T. diversifolia in forestry and agroforestry systems. Also, other Himalayan landscapes infested with T. diversifolia can generate awareness and identify the sustainable strategy for their management to conserve the indigenous biodiversity.